Serum insulin‐like growth factor‐I levels are associated with improved white matter recovery after traumatic brain injury. Issue 1 (25th July 2017) - Feeney, Claire; Sharp, David J.; Hellyer, Peter J.; Jolly, Amy E.; Cole, James H.; Scott, Gregory; Baxter, David; Jilka, Sagar; Ross, Ewan; Ham, Timothy E.; Jenkins, Peter O.; Li, Lucia M.; et al.
Abstract : Objective: Traumatic brain injury (TBI) is a common disabling condition with limited treatment options. Diffusion tensor imaging measures recovery of axonal injury in white matter (WM) tracts after TBI. Growth hormone deficiency (GHD) after TBI may impair axonal and neuropsychological recovery, and serum insulin‐like growth factor‐I (IGF‐I) may mediate this effect. We conducted a longitudinal study to determine the effects of baseline serum IGF‐I concentrations on WM tract and neuropsychological recovery after TBI. Methods: Thirty‐nine adults after TBI (84.6% male, median age = 30.5 years, 87.2% moderate–severe, median time since TBI = 16.3 months, n = 4 with GHD) were scanned twice, 13.3 months (range = 12.1–14.9) apart, and 35 healthy controls were scanned once. Symptom and quality of life questionnaires and cognitive assessments were completed at both visits (n = 33). Our main outcome measure was fractional anisotropy (FA), a measure of WM tract integrity, in a priori regions of interest: splenium of corpus callosum (SPCC) and posterior limb of internal capsule (PLIC). Results: At baseline, FA was reduced in many WM tracts including SPCC and PLIC following TBI compared to controls, indicating axonal injury, with longitudinal increases indicating axonal recovery. There was a significantly greater increase in SPCC FA over time in patients with serum IGF‐I above versus below the median for age. Only the higher IGF‐I group had significant improvements in immediate verbal memory recall over time. Interpretation: WM recovery and memory improvements after TBI were greater in patients with higher serum IGF‐I at baseline. These findings suggest that the growth hormone/IGF‐I system may be a potential therapeutic target following TBI. Ann Neurol 2017;82:30–43